I suspect that the first term should be "negative 3", ie the sequence is -3, 1, 5, 9, 13, 17, ... The nth term is 4n - 7
The nth term is 4n - 3
It is: nth term = 35-9n
The nth term is: 5-6n
The nth term is 6n+1 and so the next term will be 31
The nth term is: 3n+1 and so the next number will be 16
4 Four Qutro The correct answer is: The nth term is 4n + 1
It is increasing by 4 and the nth term is 4n+1
[ 25 - 6n ] is.
This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term
3n - 1
The nth term is: 5-2n
The sequence is simply achieved by adding 2 to each value9+2=1111+2=1313+2=1515+2=1717+2=1919+2=21so the nth term can be calculatedThe value of the nth term = the value of (nth-1 term) +2.
Just subtract 9.
t(n) = 28 - 9n
35 * * * * * That is the next term. The question, however, is about the nth term. And that is 6*n - 1
T(n) = 25 - 6n
2n + 1
7(n2-1) - 4